Pengaruh Cost Saving, Time Saving Dan Trust Terhadap Purchase Intention Melalui Perceived Value Pada Konsumen - Ilya Nafilah (Universitas PGRI Yogyakarta, 2021)
This study aims to determine the effect of cost saving, time saving and trust on purchase intention through perceived value. This research was conducted on consumers of Wedang Uwuh Beverage in Imogiri Bantul Yogyakarta. The results of this study indicate: 1) Cost Saving has a positive effect on Perceived Value, 2) Cost Saving has a positive effect on Purchase Intention, 3) Time Saving has a positive effect on Perceived Value, 4) Time Saving has a positive effect on Purchase Intention, 5 ) Trust has a positive effect on Perceived Value, 6) Trust has no positive effect on Purchase Intention, 7) Perceived Value has a positive effect on Purchase Intention.Keywords: Cost Saving, Time Saving, Trust, Purchase Intention, Perceived Value